Pengaruh Dark Triad Personality terhadap Kecenderungan Tindakan White Collar Crime - Falni, Fionica; Helmayunita, Nayang (Universitas Negeri Padang, 2024)
This research aims to analyze the influence of Machiavellian personality, narcissism and psychopathy on the tendency to commit white collar crimes. This research is associative causality research with a quantitative approach. The population in this research were Bachelor of Accounting students in 2018 and 2019 from Padang State University, Andalas University, and Bung Hatta University. The number of samples was determined using the Slovin formula to obtain 204 respondents. The data collection method uses questionnaires distributed via Google Form. The hypothesis in this study was tested using multiple linear regression analysis with IBM SPSS 25. The results showed that Machiavellian personality did not have a significant effect on the tendency to commit white collar crime. Meanwhile, narcissism and psychopathy influence the tendency to commit white collar crimes.